Sekolah Lapang Swadaya: Peningkatan Kapasitas Petani dalam Produksi PGPR dan MOL untuk Pengendalian Hayati di Lahan Padi Rawa Lebak. - Fadli, Rahmad (Universitas Aufa Royhan Di Kota Padangsidipuan, 2025)
Rice farming in lowland swamp areas still relies heavily on synthetic chemical pesticides, posing serious risks to the environment and farmers' health. This also reflects the limited adoption of biological technologies such as PGPR (Plant Growth-Promoting Rhizobacteria) and MOL (Local Microorganisms). To address this, a community service program was conducted to strengthen farmers' capacity to produce and use PGPR and MOL as biological agents for pest and disease control. Implemented through a self-help field school model, the program emphasized local wisdom and farmer independence. Activities included training, practical demonstrations, and on-site mentoring, with participatory and hands-on approaches. MOL was produced using rice washing water and golden apple snails, while PGPR was isolated from bamboo roots. The program led to positive behavioral changes, including reduced dependence on chemical pesticides and increased use of biological agents. Rice plants treated with PGPR and MOL appeared healthier and more resistant to pests and diseases. Farmers also gained the skills to independently produce these agents. Overall, the Swadaya Field School proved effective in promoting sustainable farming practices and received positive feedback from participants enthusiastic about applying PGPR and MOL biotechnology in their fields.